THE INFLUENCE OF WEATHERING TAPHONOMICAL PROCESSES ON SKELETAL PRESERVATION – SECONDARY OPENING OF GRAVES IN THE SARMATIAN SITES - Pavlovic, Tamara; Djuric, Marija (Medicinski podmladak, 2024)
After the burial of the body in the ground and the skeletonization, the skeletal remains undergo various natural taphonomic processes (caused by soil type, climate, fluvial processes, flora, fauna, etc.) that modify them and leave macroscopically visible traces on the bone surface. The state of preservation and fragmentation of skeletal material additionally change when these processes are also exposed to subsequent anthropogenic factors, such as the secondary opening of burial units, which implies the disturbance of the natural environment (geological strata, microclimate, oxidation, weathering, etc.) in which the bones were originally inhumed. In bioanthropological and forensic literature, such taphonomic processes are called subaerial weathering, causing cracks in the cortical and trabecular bone and the appearance of fracture lines and small cracks, peeling of the cortical bone, abrasion of the bone surface, and whitening of the bones by collagen. Despite the frequent occurrence of such changes, they, together with other taphonomic conditions, are still insufficiently represented and unexplored in bioanthropology and forensics. This is the case with skeletal remains from late antique necropolises on the territory of Serbia, belonging to the historical Sarmatian population that inhabited the Pannonian Plain. Although the skeletal preservation of this material is a frequent subject of discussion in bioanthropology and archaeology, previous research did not include detailed analysis of preservation and fragmentation of this material. Recent research by the Centre for Bone Biology at the Faculty of Medicine in Belgrade has shown how and to what extent post-mortem activities in the past (secondary opening of graves during looting) directly and indirectly influenced the preservation of Sarmatian skeletal material. The study showed that the skeletal remains from disturbed graves displayed many traces of taphonomic processes (cracks, fractures, peeling, bleached bones) which were caused by the continuous effect of external weathering factors (sun, rain, snow, frost) on the skeletal remains.
Keywords: Bioanthropology, human skeletal remains, taphonomy, subaerial weathering, late antique, Sarmatians